(untitled) (LEARNing Landscapes, 2012)
Weighted with the demands of graduate studies and frustrated by a writing deadline, a doctoral student is transformed by unexpected and vivid memories of a most beloved place of learning: a space containing the critical elements of energized creativity, well-worn tools, and the warmth of devoted guidance. Through interwoven reflection and the tools of meaning making, this student achieves a deep understanding of what a space to learn requires for educational inspiration.